Systematic analysis of hepatotoxicity: combining literature mining and AI language models - Bauer, Chris; Duc Dang, Long Tran; van den Beucken, Twan; Schuchhardt, Johannes; Herwig, Ralf (Frontiers in Artificial Intelligence, 2025)
BackgroundThe body of toxicological knowledge and literature is expanding at an accelerating pace. This rapid growth presents significant challenges for researchers, who must stay abreast with latest studies while also synthesizing the vast amount of published information.GoalOur goal is to automatically identify potential hepatoxicants from over 50,000 compounds using the wealth of scientific publications and knowledge.MethodsWe employ and compare three distinct methods for automatic information extraction from unstructured text: (1) text mining (2) word embeddings and (3) large language models. These approaches are combined to calculate a hepatotoxicity score for over 50,000 compounds. We assess the performance of the different methods with a use case on Drug-Induced Liver Injury (DILI).ResultsWe evaluated hepatotoxicity for over 50,000 compounds and calculated a hepatotoxicity score for each compound. Our results indicate that text mining is effective for this purpose, achieving an Area Under the Curve (AUC) of 0.8 in DILI validation. Large language models performed even better, with an AUC of 0.85, thanks to their ability to interpret the semantic context accurately. Combining these methods further improved performance, yielding an AUC of 0.87 in DILI validation. All findings are available for download to support further research on toxicity assessment.ConclusionsWe demonstrated that automated text mining is able to successfully assess the toxicity of compounds. A text mining approach seems to be superior to word embeddings. However, the application of a large language model with prompt engineering showed the best performance.